Laparoscopic major liver resection: left hepatectomy for hydatid cyst - San Martín, Gonzalo; Vanerio, Patricio; Mansilla, Sofía; Ettlin, Alejandro; Abelleira, Martín; Rodríguez, Florencia; Harguindeguy, Martín (Cirugía del Uruguay, 2024)
The case of a 45-year-old female from rural area under study for long-standing epigastralgia is presented. No notable findings on physical examiation. Imaging was compatible with hepatic hydatic cyst at left lateral segment. Given the topography, adherent to segment 4 pedicle, a left hepatectomy by laparoscopic approach was performed. Procedure without incidents. Patient presented good post-operative evolution and was discharged after 72 horas.